A Lover to Be Ashamed of: Romania in the Eyes of the Italian Political Elites - Stefano Braghiroli; Sergiu Gherghina (Journal of Social Research & Policy, 2010)
Two criminal events committed in 2007 by Romanian nationals in Italy triggered tensioned relationships between the two countries. The contemporary use of populist rhetoric in the Italian political debate contrasts sharply with the pre-2007 supportive discourses towards the Romanian accession to the EU. Such positive attitudes of the elite were driven by political reasons, mutual economic benefits, and cultural ties. This article argues that elite discourses adapted to the negative attitudes continuously displayed by the Italian public. By combining process-tracing and descriptive statistics, our study illustrates how the Italian public was highly reluctant about the EU membership of Romanians before 2007. As a result, the shift of attitudes at elite level seems driven by opportunistic reasons. While still praising Romania’s membership as an economic asset and an opportunity for the Italian business, when it comes to immigration, most Italian politicians follow and actively fuel people’s fears rather than contrasting and publicly condemning discrimination and xenophobia.